Impact of infarct location and size on clinical outcome after ST-elevation myocardial infarction treated by primary percutaneous coronary intervention. (15th February 2020) - Reindl, Martin; Holzknecht, Magdalena; Tiller, Christina; Lechner, Ivan; Schiestl, Michael; Simma, Felix; Pamminger, Mathias; Henninger, Benjamin; Mayr, Agnes; Klug, Gert; Bauer, Axel; Metzler, Bernhard; et al.
Abstract: Background: For patients suffering from acute ST-elevation myocardial infarction (STEMI), it is controversial whether infarct location predicts worse clinical outcome independently of infarct size. We therefore aimed to investigate the prognostic relevance of infarct location in relation to infarct size in STEMI patients treated with contemporary primary percutaneous coronary intervention (PCI). Methods: Cardiac magnetic resonance was performed in 355 patients with acute STEMI 3 (interquartile range [IQR]: 2–4) days after primary PCI. Infarct location, infarct size, and microvascular obstruction were assessed by late gadolinium enhancement (LGE). Patients were followed for major adverse cardiac events (MACE) at a median follow-up of 35 (IQR: 12–52) months. Results: One hundred and sixty five patients (47%) had anterior STEMI. These patients had a greater infarct size as compared to non-anterior STEMI patients (19 vs. 12% of left ventricular myocardial mass, p < .001), but no significant differences in microvascular obstruction occurrence and extent ( p = .26 and p = .09, respectively). MACE occurred in 39 patients (11%). Patients with anterior STEMI had a higher risk of MACE (hazard ratio: 2.01; 95% confidence interval: 1.05–3.83; p = .03). In multivariable analysis, infarct severity by LGE imaging but not its location was independently associated with an increased risk of MACE (hazard ratio: 1.03; 95% confidence interval: 1.01–1.06; p = .01). Conclusions: The higher rate of medium-term MACE in anterior STEMI treated with contemporary primary PCI is explained by a larger extent of myocardial damage as determined by CMR imaging without any further contribution of infarct location. Highlights: After reperfused STEMI, medium-term MACE occurred in 11%. Patients with anterior STEMI had a higher risk of MACE. Higher MACE rate in anterior STEMI is based on more pronounced myocardial damage.